Low-density stands and sparse forests in the Pokuttia Carpathians: volume, spe-cies composition, conversion measures - Debryniuk, Iu; Miklush, S. I.; Vanjurak, P. I. (Forestry Education and Science: Current Challenges and Development Prospects, 2024)
To increase the productivity and sustainability of low-density forest stands, it is most advisable to create under-canopy forest cultures, which will significantly increase the use of the potential of forest growth conditions, prevent undesirable changes in tree species, and eliminate soil sodding. To create partial forest crops under the canopy of low-density stands, shade-tolerant tree species should be used - European beech, silver fir, Norway spruce, and Douglas-fir.Special attention should be paid to sparse forests. To date, there is no officially developed system of measures that would provide ways to effectively transform sparse forests into highly productive ones. To develop such a system, first of all, it is necessary to conduct a survey of the sparse forest to determine the condition of the sites. If the plots contain specimens of valuable tree species (pine, oak, spruce, fir, ash, beech, cherry, etc.), their biological condition is good, and the trees themselves are capable of producing seeds, then they should be left on the plots for the purpose of seeding. Over the area of the plot, taking into account the remaining trees, it is necessary to cultivate the soil in strips or furrows every 3-4 m with subsequent planting in them of valuable fast-growing tree species that could quickly "come out" from under the canopy of grass and shrub vegetation.If, during the survey of sparse forests, it turns out that the area contains specimens of low-value tree species, or still valuable species, but with low biotic resistance, or specimens that have lost their reproductive capacity due to climate change or age-related changes, then a decision must be made to cut them down. In a fresh cutover area, it is necessary to carry out partial strip tillage of the soil and to plant fast-growing valuable tree species in the formed strips.The list of tree species, which are desirable to use for afforestation of sparse forests, may vary depending on the type of forest growth conditions: European larch, Japanese larch, dankeld larch; Douglas-fir, black walnut; giant fir; Scots pine, etc. Another appropriate measure is the creation in sparsely forested areas of timber plantations of fast-growing tree species with a short rotation age, which can restore the forest environment and accumulate significant volumes of wood in a relatively short period of time.